Hygienic disposal of household wastes - Reynolds, Fanny E. (My University, 1905)
Introduction: The hygienic disposal of household wastes is one of the greatest problems of the day. Inasmuch as they contain all of the excretions of the body and also garbage and refuse, and inasmuch as they may contain infections material, the safe and proper disposal of wastes is one of the first necessities of hygienic living. The health of the communities’ depends largely upon the disposal of the refuse matter Death rates have been permanently lowered since the introduction of even fairly efficient disposal of wastes. The dumping refuse upon vacant lots or around houses always leads to disease. Winds, animals, flies, and mosquitoes way become the carriers of disease. The waters are divided into three great classes. First, refuse, as ashes, dust, paper, rags and bottles. Second, Garbage, scraps of food and kitchen slops. Third, Sewage, human excreta and bath and toilet water.
Citation: Reynolds, Fanny E. Hygienic disposal of household wastes. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Refuse; Garbage; Sewage; Theses; Manuscripts (documents)